2015
DOI: 10.1007/s00894-015-2732-z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared signature of micro-hydration in the organophosphate Sarin: an ab initio study

Abstract: The infrared (IR) spectra of micro-hydrated Sarin•(H2O)n clusters containing between one and four explicit waters have been studied using ab initio density functional theory (DFT) methods. The phosphate group P=O bond vibration region (∼1270 to 1290 cm(-1)) revealed the largest frequency variation with hydration, with a frequency red shift reflecting the direct hydrogen bond formation between the P=O of Sarin and water. Small variations to the P-F stretch (∼810 to 815 cm(-1)) and the C-O-P vibrational modes (∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…All calculations were in the gas phase and correlated well with experiment for the P-O-R asymmetric stretch, however, the P=O stretches were shifted to significantly lower frequencies for GB, GD and GF. Consideration of explicit microsolvation in the current study (Table 5) has given more accurate results, in agreement with data from Alam and Pearce for GB (33), and represents a better protocol for the G-series of CWAs. Indeed, it may be that microsolvation is a more appropriate method to model other CWAs and their simulants, however, due to the extended computational time required, it was not considered in this study.…”
Section: Comparison With Other Simulationssupporting
confidence: 88%
“…All calculations were in the gas phase and correlated well with experiment for the P-O-R asymmetric stretch, however, the P=O stretches were shifted to significantly lower frequencies for GB, GD and GF. Consideration of explicit microsolvation in the current study (Table 5) has given more accurate results, in agreement with data from Alam and Pearce for GB (33), and represents a better protocol for the G-series of CWAs. Indeed, it may be that microsolvation is a more appropriate method to model other CWAs and their simulants, however, due to the extended computational time required, it was not considered in this study.…”
Section: Comparison With Other Simulationssupporting
confidence: 88%
“…the experimental spectra, typically around 1.00-1.05, apparently to compensate for anharmonic effects. [38][39][40][41][42][43][44][45] In line with those findings, in our study a fair agreement in the position of part of the IRMPD bands is already observed in the IR spectra predicted computationally without scaling. Nevertheless, the best agreement between the experiment and the oB97X-D, CAM-B3LYP and MP2 computations is obtained if the vibrational modes with participation of the phosphate group are singled out and their frequencies are left unscaled, while a scaling factor of 0.97 is applied to the frequencies of the vibrational modes with a marginal participation of the phosphate group, namely those of the backbones of the ribose and guanine moieties and of the guanidinium guest cation (e.g., C-C, C-N or C-O stretching vibrations, CH n bending vibrations, see Table 1).…”
Section: B Quantum Chemical Calculationssupporting
confidence: 92%
“…Hydrated microclusters formed by the nerve agent sarin have been probed to understand the impact of adding discrete water molecules to its binding energies and the vibrational wavenumber of the phosphate-water hydrogen bond (H-bond). Different nerve agents and their simulants have been microhydrated to determine the extent to which the simulants mimic the properties of the original CWAs in solution .…”
Section: Introductionmentioning
confidence: 99%